(untitled) (Annals of Medical Research, 2021)
Aim: The laboratory findings are non-specific in Rheumatoid arthritis (RA). We have based our study on this idea and chose cytokines and chemokine to evaluate ; we then tried to establish a relationship between the progress of the disease and the levels of these molecules before and 3-6 months after the TNF-α blocker treatment.Material and Methods: A total of 34 RA patients (28 females, 6 males) who were diagnosed with RA and received TNF-α blocker therapy were included in the study.Blood samples were drawn from the patients before the TNF-α treatment began and then in the following 3rd and 6th months of the treatment.Results: The mean age of the study group is 49.15±11.03. the mean disease period is 9.77±6.29 years and the mean treatment period is 6.88±4.33 years. 84.6% (n=22) of the study group is female and 15.4% (n=4) is male.Patients with good treatment response to TNF-α blocker treatment were younger than the patients with medium treatment response. The increase of mean hemoglobin (Hgb) levels between 0 and 6 months were statistically meaningful (both p0.05).Conclusion: In RA patients receiving TNF-α blocker therapy. cytokine levels decreased with treatment.The relationship between IL-6 and DAS28 change in the pre-treatment and 6-month period may help the clinician to show the disease activity and to guide the course of the disease.